2013
DOI: 10.1215/10642684-2279906
|View full text |Cite
|
Sign up to set email alerts
|

No Taste for Rough-and-Tumble Play

Abstract: This article explores the role of sport in the regulation of boys' gender nonconformity. More specifically, it looks at the way sport contributes to producing the pronounced anti-effeminacy that pervades North American culture. Sport is a huge conceptual category that captures activities as diverse as NFL football, minor league co-ed softball, and recreational jogging. Sport is something people do, and it is something people watch. It produces intense physical pleasures, yet also pain, leading to, for example,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…19The injurious nature of these speech acts flowed from the accumulative force over time of dominant discourses about sexuality and gender including heteronormativity and served as resources for the meanings attached to these words. Briefly, these speech acts resonate, especially in sport contexts, because they are embedded in a history in which modern sport was constructed to emphasize specific desirable practices of embodied heteromasculinity (Adams, 2013). Practices associated with weakness such as those attributed to gay men/homosexuality and women/femininity were and continue to be devalued and often form the base for injurious speech acts (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19The injurious nature of these speech acts flowed from the accumulative force over time of dominant discourses about sexuality and gender including heteronormativity and served as resources for the meanings attached to these words. Briefly, these speech acts resonate, especially in sport contexts, because they are embedded in a history in which modern sport was constructed to emphasize specific desirable practices of embodied heteromasculinity (Adams, 2013). Practices associated with weakness such as those attributed to gay men/homosexuality and women/femininity were and continue to be devalued and often form the base for injurious speech acts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The devaluing of what is associated with 'feminine' served as a subtext of many of the homonegative speech acts in this study and supports Pascoe's (2007Pascoe's ( , 2013 contention that research on these speech acts has neglected its gendered content, or rather its femmephobia. Femmephobia, sometimes called effeminephobia, is a disdain for or a systematic devaluation of femininity and reflects misogyny (Adams, 2013;Annes and Redlin, 2012;Hoskin, 2019;Richardson, 2009). If gender equality would be a current dominant discourse in sport then a gay aesthetic that associates specific and bodily enactments with femininity would not be constructed as an insult.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many contextual and individual difference factors may magnify men’s bias against feminine men. Several studies showed that anti-effeminacy bias is stronger among men who belong to masculine coalitions or subcultures (e.g., contact sports teams, military, street gangs; Adams, 2013 ; Herek, 1993 ; Lingiardi et al, 2005 ) and who adhere to traditional norms of masculinity (e.g., Keiller, 2010 ; Wilkinson, 2004 ).…”
Section: Individual Differences In Masculine Honor Idealsmentioning
confidence: 99%
“…Radcliffe continued to run throughout her pregnancies, and in doing so, she was represented as a role model for other pregnant women (McGannon et al, 2012). Her pregnancy and motherhood shifted media discourses away from her status as an elite athlete (Walton, 2010) to her status as a fitness role model (McGannon et al, 2012), underscoring Mary Louise Adams’s observation that “[d]espite huge increases in the numbers of women and girls participating in sport over the past few decades, ‘sport’ has yet to become a gender-neutral noun” (2013, p. 521). In keeping with ideological portrayal of women athletes (Birrell & Theberge, 1994), Torres’s and Radcliffe’s status as mothers is highlighted above their status as elite athletes, reinforcing their motherhood as equal to heterosexuality and womanhood, while also further perpetuating the notion that fitness—not athleticism—equates to womanhood.…”
Section: Media Coverage Of Women’s Sport: Athletic or Fit?mentioning
confidence: 99%